ALK7 expression in prolactinoma is associated with reduced prolactin and increased proliferation. Issue 9 (September 2018) - Principe, M; Chanal, M; Karam, V; Wierinckx, A; Mikaélian, I; Gadet, R; Auger, C; Raverot, V; Jouanneau, E; Vasiljevic, A; Hennino, A; Raverot, G; et al.
Abstract : Prolactinoma represents the most frequent hormone-secreting pituitary tumours. These tumours appear in a benign form, but some of them can reach an invasive and aggressive stage through an unknown mechanism. Discovering markers to identify prolactinoma proliferative and invading character is therefore crucial to develop new diagnostic/prognostic strategies. Interestingly, members of the TGFβ-Activin/BMP signalling pathways have emerged as important actors of pituitary development and adult function, but their role in prolactinomas remains to be precisely determined. Here, using a heterotopic allograft model derived from a rat prolactinoma, we report that the Activins orphan type I receptor ALK7 is ectopically expressed in prolactinomas-cells. Through immunohistological approaches, we further confirm that normal prolactin-producing cells lack ALK7-expression. Using a series of human tumour samples, we show that ALK7 expression in prolactinomas cells is evolutionary conserved between rat and human. More interestingly, our results highlight that tumours showing a robust expression of ALK7 present an increased proliferation as address by Ki67 expression and retrospective analysis of clinical data from 38 patients, presenting ALK7 as an appealing marker of prolactinoma aggressiveness. Beside this observation, our work pinpoints that the expression of prolactin is highly heterogeneous in prolactinoma cells. We further confirm the contribution of ALK7 in these observations and the existence of highly immunoreactive prolactin cells lacking ALK7 expression. Taken together, our observations suggest that Activin signalling mediated through ALK7 could therefore contribute to the hormonal heterogeneity and increased proliferation of prolactinomas.